2021
DOI: 10.1038/s41467-021-21213-4
|View full text |Cite
|
Sign up to set email alerts
|

A genome-wide CRISPR screen identifies host factors that regulate SARS-CoV-2 entry

Abstract: The global spread of SARS-CoV-2 is posing major public health challenges. One feature of SARS-CoV-2 spike protein is the insertion of multi-basic residues at the S1/S2 subunit cleavage site. Here, we find that the virus with intact spike (Sfull) preferentially enters cells via fusion at the plasma membrane, whereas a clone (Sdel) with deletion disrupting the multi-basic S1/S2 site utilizes an endosomal entry pathway. Using Sdel as model, we perform a genome-wide CRISPR screen and identify several endosomal ent… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
301
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 237 publications
(320 citation statements)
references
References 65 publications
16
301
3
Order By: Relevance
“…To discriminate the two S protein activation pathways, we included the . This explains why SARS-CoV-2 passaging in Vero E6 cells regularly leads to emergence of viruses bearing substitutions or deletions in the S1/S2 loop [45][46][47][48][49][50][51][52].…”
Section: Loop Deletion Mutants Of Sars-2-s Show Enhanced Cathepsin-dependent Entry Explaining Their Emergence In Vero Cellsmentioning
confidence: 99%
See 2 more Smart Citations
“…To discriminate the two S protein activation pathways, we included the . This explains why SARS-CoV-2 passaging in Vero E6 cells regularly leads to emergence of viruses bearing substitutions or deletions in the S1/S2 loop [45][46][47][48][49][50][51][52].…”
Section: Loop Deletion Mutants Of Sars-2-s Show Enhanced Cathepsin-dependent Entry Explaining Their Emergence In Vero Cellsmentioning
confidence: 99%
“…When unprimed, SARS-2-S pseudoviruses are strongly boosted towards the cathepsin B/L route. This likely explains the replication advantage of loop-deletion SARS-CoV-2 mutants in cathepsin L-rich Vero E6 cells [45][46][47][48][49][50][51][52]. The non-covalently linked S1/S2 form is less stable and a plausible disadvantage for endosomal entry.…”
Section: Plos Pathogensmentioning
confidence: 99%
See 1 more Smart Citation
“…P681H is at the S1/S2 cleavage site and could affect the efficiency of furin cleavage. We and others have previously shown that efficient cleavage of S at this site enhances transmissibility and pathogenicity of SARS-CoV-2 (Johnson et al, 2021;Peacock et al, 2020;Zhu et al, 2021). B.1.1.7 also harbours mutations of interest in other genes including a premature stop codon in ORF8, an accessory gene that likely enables immune evasion (Zhang et al, 2020), and a 3 amino acid deletion in NSP6, one of several proteins associated with virus regulation of the innate immune response (Xia et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…This fusion function of S is dependent on its cleavage by host cell proteases, which occurs either following attachment of virions to the host cell membrane or during virion maturation and egress [3, 7, 8]. Strikingly, SARS-CoV-2 S harbors a furin-cleavage site [9], and pre-activation ‘priming’ of S by furin-like proteases increases fusion-dependent entry efficiency of the virus at the plasma membrane following further cleavage by host TMPRSS2 [10-13]. Other SARS-CoV-2 virion components include the Membrane (M) protein that confers shape and support to the virus particle and interacts with both S and the Nucleoprotein (N; which coats the viral RNA genome [14, 15]), and the Envelope (E) protein, a small membrane protein that both drives virion assembly and budding [16], and has ion channel activity linked to viral pathogenesis [17].…”
Section: Introductionmentioning
confidence: 99%